Decarbonization of Costa Rica's agriculture, forestry and other land uses sectors: An application of the IEEM+ESM approach - Onil Banerjee; Martín Cicowiez; Renato Vargas; Edmundo Molina-Pérez; Žiga Malek (Inter-American Development Bank (IDB), 2021)
This paper evaluates the economic and environmental impacts of implementing Costa Ricas Decarbonization Plan, focusing specifically on the Agriculture, Forestry and Other Land Uses (AFOLU) sectors. To do so, we apply the Integrated Economic-Environmental Modeling (IEEM) framework for Costa Rica, linked with high resolution spatial land use land cover and ecosystem services modeling (IEEMESM). This is the first economy-wide analysis of Costa Ricas Decarbonization Plan that integrates both economic and ecosystem services impacts. Such an integrated approach is critical for understanding cross-sectoral implications of decarbonization despite the sector-specific focus of AFOLU, while considering the impacts on future ecosystem services flows and wealth. Our results indicate that the positive cumulative wealth impacts of the full decarbonization of Costa Ricas AFOLU sectors are on the order of US8,747 million by 2050 and generally enhances the future flow of ecosystem services. Decarbonization of AFOLU is pro-poor, lifting 4,530 out of poverty by 2050. From a public investment perspective, decarbonization generates economic returns of US1,114 million when natural capital and environmental quality are considered. The IEEMESM Platform developed in this paper provides a strong foundation for future analysis and refinement of proposed decarbonization strategies for the country, while weighing the relative costs and benefits of the economic, environmental and social dimensions in an integrated way.
Keywords: C68; Q5; O13; Q54; 330; Integrated Economic-Environmental Modeling (IEEM) Platform; dynamic computable general equilibrium (CGE) model; ecosystem services modeling; agriculture; climate change; decarbonization